2011
DOI: 10.1177/0018720810397353
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Graphical Objects on Computer Screens

Abstract: The three-phase model provides a framework for ergonomists to evaluate new positioning techniques and can explain their deficiencies. The model provides a means to analyze tasks and enhance interaction during positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Figure 4: ET modeled by log 2 (p/t + 1) Confirmation time was inversely proportional to angular tolerance and followed Piéron's Law for the reaction time to a stimulus, suggesting that, during this phase, participants were primarily focused on recognizing that the sector is orientated. In a previous study, one the authors of this paper has demonstrated that the power (β) in Piéron's Law for a one degree of freedom experiment was 0.63 and for a two degrees of freedom experiment was 0.67 (Pastel, 2011). The powers laid in each others 95% confidence intervals.…”
Section: E T (Ms)mentioning
confidence: 71%
See 3 more Smart Citations
“…Figure 4: ET modeled by log 2 (p/t + 1) Confirmation time was inversely proportional to angular tolerance and followed Piéron's Law for the reaction time to a stimulus, suggesting that, during this phase, participants were primarily focused on recognizing that the sector is orientated. In a previous study, one the authors of this paper has demonstrated that the power (β) in Piéron's Law for a one degree of freedom experiment was 0.63 and for a two degrees of freedom experiment was 0.67 (Pastel, 2011). The powers laid in each others 95% confidence intervals.…”
Section: E T (Ms)mentioning
confidence: 71%
“…This restricts by necessity the experimental studies to relatively large tolerances if the positioned object is to be visible. Pastel (2011) illustrated that the compensation of object width by using tolerance in ID F is not sufficient at small tolerances. The model for MT to precisely position objects required an additional term in inverse tolerance.…”
Section: Id F = Log 2 (A/t + 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Blocking of the target conditions certainly is not necessary. Pastel (2011) is an example of a study that randomizes the target conditions. However, of the nine studies cited in Soukoreff and MacKenzie (2004) as examples that have followed ISO 9241-9, the six that we could obtain and that included enough detail to determine how the conditions were ordered, all blocked target conditions.…”
Section: Issue 1: Influence Of Design Choices On the External Validitmentioning
confidence: 99%